2003
DOI: 10.1021/jo030157k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Intermolecular Ortho-Arylation of Phenols

Abstract: The use of rhodium catalysts such as [RhCl(PPh3)3] or [[RhCl(COD)]2] with PiPr2(OAr) or P(NMe2)3 co-catalysts allows the ortho-selective intermolecular arylation of phenols. The reaction proceeds via orthometalation of P-OAr groups and then transesterification liberates the product phenol. When 2-substituted phenols are used as substrates, [RhCl(PPh3)3]/iPr2(OAr) mixtures are typically the catalysts of choice, whereas for substrates without 2-substitution [[RhCl(COD)]2]/P(NMe2)3 mixtures tend to give better re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(88 citation statements)
references
References 23 publications
0
84
0
4
Order By: Relevance
“…[202,203] As a result, the specific phosphinite co-catalyst needs to be prepared for each individual substrate prior to catalysis to avoid formation of undesired and difficult to separate by-products. This limitation was independently addressed by Oi, Inoue et al [204] as well as by Bedford and Limmert, [205] with the use of inexpensive P(NMe 2 ) 3 as the cocatalyst. Thus, a system comprising [{RhCl(cod)} 2 ] and P-(NMe 2 ) 3 proved complementary to the previously reported phosphinite-based catalyst, in that efficient functionalizations of ortho-unsubstituted phenols proved viable (Scheme 112).…”
Section: Rhodium-catalyzed Direct Arylationmentioning
confidence: 99%
“…[202,203] As a result, the specific phosphinite co-catalyst needs to be prepared for each individual substrate prior to catalysis to avoid formation of undesired and difficult to separate by-products. This limitation was independently addressed by Oi, Inoue et al [204] as well as by Bedford and Limmert, [205] with the use of inexpensive P(NMe 2 ) 3 as the cocatalyst. Thus, a system comprising [{RhCl(cod)} 2 ] and P-(NMe 2 ) 3 proved complementary to the previously reported phosphinite-based catalyst, in that efficient functionalizations of ortho-unsubstituted phenols proved viable (Scheme 112).…”
Section: Rhodium-catalyzed Direct Arylationmentioning
confidence: 99%
“…[202,203] Im Ergebnis muss der jeweilige Phosphinit-Cokatalysator für jedes spezielle Substrat eigens hergestellt werden, um die Bildung unerwünschter und schwierig abzutrennender Nebenprodukte zu vermeiden. Oi, Inoue et al [204] sowie Bedford et al [205] fanden unabhängig voneinander, dass diese Einschränkung durch die Verwendung von preiswertem P(NMe 2 ) 3 als Cokatalysator überwunden werden kann. Ein solches Katalysatorsystem aus [RhCl(cod)] 2 und P(NMe 2 ) 3 ergänzt somit den bereits beschriebenen Phosphinit-Katalysator, indem es die Funktionalisierung von in ortho-Position unsubstituierten Phenolen ermöglicht (Schema 112).…”
Section: Rhodiumkatalysierte Direkte Arylierungenunclassified
“…The important feature of this methodology is the remarkably mild reaction conditions and excellent functional group tolerance. [73][74][75][76][77] In a recent report the application of a strong paccepting ligand P[(OCH(CF 3 ) 2 ) 3 ] proved viable for the rhodium-catalyzed direct arylations of unactivated arene 46 under microwave irradiations. 78,79 The absence of coordinating moiety resulted in a mixture of ortho-48 and para-substituted 49 regioisomers (Scheme 10), which suggested that an electrophilic aromatic substitution type-mechanism was operative.…”
Section: Electrophilic Aromatic Substitution (S E Ar Mechanism)mentioning
confidence: 99%